Self-objectification, cyberbullying experiences and wellbeing among Malaysian young adults: personal values as moderator - Teng, Jaclyn Hui Jie * (2024)
Sexualizing experiences via interpersonal and media encounters causes self-objectification (SO), which is placing an inner gaze on one’s own appearance. In recent years, the surge of image-focused social networking sites (SNSs) fuels appearance comparisons due to the constant online exposure of mainstream appearance ideals. This leads to the internalization of the standard of attractiveness, followed by SO, which manifests through habitual appearance monitoring (i.e., body surveillance) based on mainstream and culturally specific standards of attractiveness. However, no study had examined culture-specific SO experiences in Malaysia. In addition, the increased SNSs use was also associated with negative well-being and cyberbullying. On the other hand, behaviour planning (e.g., SNSs use and cyberbullying behaviours) are likely to depend on personal values. Thus, the association between SO, personal values, cyberbullying experiences and wellbeung among Malaysian young adults require further examination. The current study sought to explore the standard of attractiveness in Malaysia as indicators of culture-specific SO through two-stage of data collection. The first stage through qualitative focus group interviews among 36 Malaysian young adults to discuss the standard of attractiveness and its associated pressures among Malaysian young adults. This resulted in six indicators of culture-specific standards of attractiveness (i.e., body size and shape, skin tone, skin texture, hair, height, facial features). These indicators were incorporated to modify the culture-specific body monitoring scale for the second stage of data collection through online survey. In the second stage, a total of 206 Malaysian young adults (Mage=22.82; SDage=3.313) participated in an online survey to examine the relationships between SO (i.e., general and culturally specific), psychological distress, cyberbullying, and personal values (i.e., self-transcendence and conservation). Results indicated that general SO predicted lower life satisfaction (β=-.387, p<.001), whereas culture-specific SO predicted psychological distress (β=.374, p<.001). The relationship between culture-specific SO and psychological distress was partially mediated by cyberbullying experiences (β=.097, p=.008). The negative effect of SO on wellbeing is heightened by cyberbullying experiences, but only accounting for culturally specific SO. Further analysis did not support the moderated-mediation hypotheses, such that personal values (i.e., self-transcendence and conservation) were not significant moderators for the mediational effect of cyberbullying experiences on SO and wellbeing. The current study provided support to the application of the objectification theory framework as SO predicted negative wellbeing among Malaysian young adults. The general and culture-specific SO predicted different outcomes of wellbeing as according to past studies; this finding demonstrated the need to incorporate culturally-specific measures to represent SO for non-White samples. This study also revealed the mediating role of cyberbullying experiences on SO and wellbeing, which highlights the threat of exposures to online harassments on frequent SNS users especially young adults. Outcome of this study reveals how the external influences (e.g., family, peers, media) exerted appearance-related pressures that manifested in appearance-monitoring behaviors and feelings of body shame. This emphasizes the importance of reducing sexualizing comments and content in interpersonal interactions to target the root cause of SO processes, as part of the strategies targeting eating disorders and other mental health risks.